2006
DOI: 10.1124/jpet.106.107482
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of Heme Oxygenase Provides Vascular Protection in an Animal Model of Diabetes through Its Antioxidant and Antiapoptotic Effects

Abstract: Heme oxygenase (HO) plays a critical role in the regulation of cellular oxidative stress. The effects of the reactive oxygen species scavenger ebselen and the HO inducers cobalt protoporphyrin and stannous chloride (SnCl 2 ) on HO protein levels and activity, indices of oxidative stress, and the progression of diabetes were examined in the Zucker rat model of type 2 diabetes. The onset of diabetes coincided with an increase in HO-1 protein levels and a paradoxical decrease in HO activity, which was restored by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 39 publications
8
87
0
1
Order By: Relevance
“…HO-1 overexpression or induction, and CO donors might alter this ratio in favor of bcl-X L thus inhibiting cell death. In streptozotocin-induced diabetic kidney, HO-1 induction increased bcl-X L expression, but failed to modulate bax expression [26]. Similarly, CoPPIX has been shown to induce bcl-X L expression [53].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…HO-1 overexpression or induction, and CO donors might alter this ratio in favor of bcl-X L thus inhibiting cell death. In streptozotocin-induced diabetic kidney, HO-1 induction increased bcl-X L expression, but failed to modulate bax expression [26]. Similarly, CoPPIX has been shown to induce bcl-X L expression [53].…”
Section: Discussionmentioning
confidence: 98%
“…Bilirubin exerts toxic effects at high concentrations. But at lower concentrations it exerts anti-oxidant effects efficiently scavenging peroxyl radicals [25], and both biliverdin and bilurubin have been shown to inhibit p38 MAPK activation [26].…”
Section: Methodsmentioning
confidence: 99%
“…[45][46][47][48][49] The decrease in HO-1 expression as a result of increased glucose levels, increases ROS, endothelial cell death, endothelial progenitor function and insulin resistance. 48,[50][51][52] Increased ROS levels and decreased levels of serum adiponectin thereby contribute to the pathogenesis of insulin resistance. 18,53 Humans and rodents deficient in either HO-1 or HO-2 develop vascular dysfunction and die prematurely.…”
Section: Discussionmentioning
confidence: 99%
“…First strand cDNA was synthesized from 1 µg of total RNA employing the RevertAid First Strand cDNA Synthesis Kit (ThermoScientific, Loughborough, UK) and an oligo(dT) [12][13][14][15][16][17][18] primer as reverse primer. Then, target genes were amplified by real-time PCR using GoTaq qPCR Master Mix (Promega, Southampton, UK) in Applied Biosystems 7500 Real-Time PCR System (ThermoScientific, Loughborough, UK).…”
Section: Total Rna Isolation and Gene Expression Analysismentioning
confidence: 99%
“…About the anti-apoptotic effects of HO-1, Abraham et al [11] have previously reported that the overexpression of HO-1 in human dermal microvessel endothelial cells prevented high glucose-mediated slowdown of cell cycle progression and increase in apoptosis [11]. Utilizing Zucker diabetic fat rats (ZDF), it has also been reported that the induction HO-1expression at the early stages of diabetes using cobalt protoporphyrin (CoPP) and stannous chloride (SnCl 2 ) imporved blood pressure and reduced endothelial cell sloughing and strongly upregulated anti-apoptotic signals including Bcl-xl and Bcl-2 [12].…”
Section: Introductionmentioning
confidence: 99%